1977
DOI: 10.1111/j.1600-065x.1977.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

IgD and B Cell Differentiation

Abstract: SDS-PAGE= scxlium dodecyl sulfate polyacrylamide gel electrophoresis FACS = fluorescent activated cell sorter PFC = plaque-forming cell FCS = fetal calf serum BSA = bovine serum albumin C = complement LPS = lipopolysaccharide TD = thymus-dependent TI = thymus-independent ' SRBC = sheep red blood cells ' CR = complement receptorThe discovery of murine IgDThe early biochemical studies of cell surface immunoglobulin (Ig) on murine lymphocytes revealed that IgM in its monomeric form was the major cell surface Ig (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(37 citation statements)
references
References 79 publications
3
34
0
Order By: Relevance
“…These results are consistent with the reports of other investigators that surface IgD, in contrast to surface IgM, is extremely susceptible to proteolysis (30,31 The phenomenon of loss of surface IgD from B cells has been described by several investigators to occur after stimulation of mature B cells by mitogens or antigens and is presumably the result of differentiation of B cells, which later become IgM-, IgG-, and IgA-secreting cells (20). In several recent studies, researchers have shown that spleen lymphocytes in NZB mice have markedly decreased levels of surface IgD relative to IgM (3,4,33).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the reports of other investigators that surface IgD, in contrast to surface IgM, is extremely susceptible to proteolysis (30,31 The phenomenon of loss of surface IgD from B cells has been described by several investigators to occur after stimulation of mature B cells by mitogens or antigens and is presumably the result of differentiation of B cells, which later become IgM-, IgG-, and IgA-secreting cells (20). In several recent studies, researchers have shown that spleen lymphocytes in NZB mice have markedly decreased levels of surface IgD relative to IgM (3,4,33).…”
Section: Discussionsupporting
confidence: 93%
“…They first express only IgM as antigen receptor on their surface. When leaving the bone marrow as mature B cells, they coexpress a second antigen receptor, IgD, of the same specificity as IgM (1)(2)(3). Naive B cells and B cells located in primary follicles express both IgD and IgM, whereas splenic marginal-zone B cells and a large proportion of memory B cells only express IgM (5,6).…”
mentioning
confidence: 99%
“…This observation prompted much new research that led to the finding of an IgD homologue on B cells in many animals (13). Evidence is rapidly accumulating to support the idea that membrane IgD plays a key role in lymphocyte activation, differentiation, and proliferation (14).…”
mentioning
confidence: 99%